A risk-based internal audit approach for the public sector: evidence from Greece. (14th June 2019) - Politis, Yannis
The roles and responsibilities of internal audit departments have evolved over the years in order to find new ways to add value to organisations. Their role has widened from the management of financial risks to the risk management of everything. However, very few academic papers have been developed addressing risk-based internal auditing, especially in the public sector. This paper presents a risk-based approach to conduct internal audits in the public sector based on the new roles and objectives of the internal audit function and the experience gained with the reform of Greek public administration. The proposed approach has been implemented in a Greek local authority and the empirical study presented can serve as an example for public, and not only, organisations in order to conduct risk-based audits in a structured way.